Analisis Capaian Rombongan Belajar di Provinsi Lampung Tahun 2018 Dalam Upaya Implementasi Permendikbud Nomor 17 Tahun 2017 - Novrian Satria Perdana (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2018)
This study is to analyze the achievement of study groups in Lampung in 2018 in the effort of implementation of Permendikbud Number 17 year 2017 to achieve the effectiveness of learning. The results of this study are: 1) For the elementary level of student ratio every rombel is the largest city, for junior high school ratients every rombel is the largest city, for high school student ratio every rombel is the largest city, and for the highest student ratio per student rombel level is West Coast District; 2) Only elementary school has rombel student ratio exceed Permendikbud Number 17 Year 2017; and 3) There are still some students who have National Examination value below National and Provincial Average, and high standard deviation result of National Examination result. This indicates that students' understanding of learning is still uneven across regions and is caused by the high number of students every rombel.